2021
DOI: 10.3390/app11157113
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation of Two Side-by-Side Heavy Particles of Different Density in a Shear-Thinning Fluid with Viscoelastic Properties

Abstract: Particle sedimentation has widely existed in nature and engineering fields, and most carrier fluids are non-Newtonian. Recently, the manipulation of a settling particle in liquid has been a topic of high interest to those involved in engineered processes such as composite materials, pharmaceutical manufacture, chemistry and the petroleum industry. Compared with Newtonian fluid, the viscosity of non-Newtonian fluid is closely related to the shear rate, leading to a single settling particle having different dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The shear thinning and viscoelastic properties of the PAAm solution are specically described in our recent paper. 23 The density of the PAAm solution is 1005 kg m −3 , which is very close to that of water. The shear thinning and viscoelastic properties of 0.5% PAAM solution are shown in Fig.…”
Section: Experimental Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…The shear thinning and viscoelastic properties of the PAAm solution are specically described in our recent paper. 23 The density of the PAAm solution is 1005 kg m −3 , which is very close to that of water. The shear thinning and viscoelastic properties of 0.5% PAAM solution are shown in Fig.…”
Section: Experimental Methodsmentioning
confidence: 72%
“…The shear thinning and viscoelastic properties of the PAAm solution are specifically described in our recent paper. 23 …”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and Lin [16] reviewed multiphase flow with self-driven particles and focused on the interactions between selfpropelled/self-rotary particles and passive particles, the aggregation, phase separation, and sedimentation of squirmers, the effect of rheological properties on its motion, and the kinematic characteristics of axisymmetric squirmers. Yang et al [17] studied the trajectories and velocities of two side-by-side particles of different densities settling in a shear-thinning fluid with viscoelastic properties. They showed that the wake of the heavier particle could attract or rebound the light particle due to the shear-thinning or viscoelastic property of the fluid, and the sedimentation of the light particle could induce the distinguishable transverse migration of the heavy one.…”
Section: Foundation and Application Of Multiphase Flow In Microfluidicsmentioning
confidence: 99%
“…However, in creeping flow regimes, the error increases to as large as 60% in polymer solutions , because most of the polymer solutions encountered in fluidized state applications possess elastic nature, and investigators have not taken into account the effect of elasticity. Further, flow behavior of the fluidizing agents exploited in food processing, biomedical applications, fluidized bed agglomeration, , chemical and pharmaceutical applications, marine hydrate exploitation, soil bed fluidization, and oil recovery processes exhibits viscoelastic character. , …”
Section: Introductionmentioning
confidence: 99%